Design thinking–mediated joyful learning through AI-interactive media: An applied study on enhancing higher-order thinking skills in secondary education - Alfha Edison; Ida Dwijayanti; F.X. Didik Purwosetiyono (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: The growing demand for higher-order thinking skills (HOTS) in secondary education has exposed the limitations of conventional instructional media that remain procedural, teacher-centered, and cognitively shallow. Although digital learning tools are increasingly adopted, many fail to explain how pedagogical mechanisms such as design thinking and joyful learning interact with AI-assisted media to produce meaningful cognitive gains. Aims: This study aims to examine the role of design thinking as a mediating pedagogical mechanism within AI-interactive learning media to enhance students’ higher-order thinking skills. Methods: An applied research and development study was conducted using an ADDIE framework integrated with design thinking stages. Sixty secondary school students were assigned to experimental and control groups. Data were collected through expert validation instruments, HOTS tests aligned with revised Bloom’s taxonomy, observation sheets, and student response questionnaires. Quantitative analyses included validity indices, N-gain scores, and independent sample t-tests, supported by qualitative thematic interpretation. Results: The AI-interactive media demonstrated high validity and practicality. Students in the experimental group achieved a high N-gain score (0.76), significantly outperforming the control group. Improvements were consistent across HOTS levels, particularly in creative and evaluative thinking, supported by strong engagement indicators associated with joyful learning features. Conclusion: The findings indicate that design thinking–mediated joyful learning, when operationalized through AI-interactive media, functions as a cognitive scaffold rather than merely a technological enhancement. This approach systematically promotes deeper reasoning, learner autonomy, and sustained cognitive engagement. The study offers an applied pedagogical model that extends beyond media development by explaining the mechanism through which AI-supported interactivity amplifies higher-order thinking. These results provide robust empirical evidence for integrating design thinking and joyful learning as foundational principles in future educational technology design and applied learning research.